The Utility of the WHO ICD-10-AM Pastoral Intervention Codings Within Religious, Pastoral and Spiritual Care Research - Carey, Lindsay B. (Journal of religion and health, 2015)
The World Health Organization (WHO) ‘Pastoral Intervention Codings’ were first released in 2002 as part of the ‘International Statistical Classification of Diseases and Related Health Problems’ (WHO 2002). The purpose of the WHO pastoral intervention codings (colloquially abbreviated as ‘WHO-PICs’) was to record and account for the religious, pastoral and/or spiritual interventions of chaplains and volunteers providing care to patients and other clients experiencing religious and/or spiritual health and well-being issues. The intent of such WHO codings was to provide information in five areas: statistical, research, clinical, education and policy. The purpose of this paper predominantly accounts for research although it does intersect and relate to other WHO priorities. Over the past 10 years, research by the current and associated authors to test the efficacy of the WHO-PICs has been implemented in a number of different health and welfare contexts that have engaged chaplaincy personnel. In summary, while the WHO-PICs are yet to be more widely utilized internationally, the codings have largely proven to be valuable indices appropriate to a variety of contexts. Research utilizing the WHO-PICs, however, has also revealed the necessity for a number of changes and inclusions to be implemented. Recommendations concerning the future utilisation of the WHO-PICs are made, as are recommendations for these codings to be further developed and promoted by the WHO, so as to more accurately record religious, pastoral and spiritual interventions.